2019
DOI: 10.1021/acs.est.9b04047
|View full text |Cite
|
Sign up to set email alerts
|

Defluorination of Perfluorooctanoic Acid (PFOA) and Perfluorooctane Sulfonate (PFOS) by Acidimicrobium sp. Strain A6

Abstract: Incubations with pure and enrichment cultures of Acidimicrobium sp. strain A6 (A6), an autotroph that oxidizes ammonium to nitrite while reducing ferric iron, were conducted in the presence of PFOA or PFOS at 0.1 mg/L and 100 mg/L. Buildup of fluoride, shorter-chain perfluorinated products, and acetate was observed, as well as a decrease in Fe­(III) reduced per ammonium oxidized. Incubations with hydrogen as a sole electron donor also resulted in the defluorination of these PFAS. Removal of up to 60% of PFOA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
209
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(240 citation statements)
references
References 48 publications
1
209
1
Order By: Relevance
“…In the scientific literature, a few studies have suggested possible avenues for C-F bond dissociation in the presence of additional electrons. [20][21][22] However, the majority of these studies carried out their analysis after the degradation has occurred, and specific mechanistic details of PFAS degradation are less understood. Although a few computational studies have addressed possible degradation of PFASs with excess electrons, 20 these studies were limited to static (i.e., nondynamic or stationary) electronic structure methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, a few studies have suggested possible avenues for C-F bond dissociation in the presence of additional electrons. [20][21][22] However, the majority of these studies carried out their analysis after the degradation has occurred, and specific mechanistic details of PFAS degradation are less understood. Although a few computational studies have addressed possible degradation of PFASs with excess electrons, 20 these studies were limited to static (i.e., nondynamic or stationary) electronic structure methods.…”
mentioning
confidence: 99%
“…Inspired by recent works demonstrating that reduction processes (i.e., the addition of electrons) can degrade PFASs, [20][21][22] we studied the degradation dynamics of both PFOA and PFOS in the presence of excess electrons. To avoid any spurious selfinteraction effects, which are usually observed with semi-local functionals such as PBE, we have included self-interaction corrections in all our MD simulations (further details are given in the Supplementary Information).…”
mentioning
confidence: 99%
“…Further, Huang and Jaffé (2019) reported on the ability of Acidimicrobium sp. A6 strain to perform bioreductive defluorination of both PFOA and PFOS, using either ammonium or hydrogen as an electron donor [57]. From these examples, it is evident how the interaction between poly-fluorinated alkyl substances and microorganisms takes place, however, leading to the generation of short-chain fully fluorinated compounds for which any biotic reaction aimed to their breakdown is not described.…”
Section: Resultsmentioning
confidence: 99%
“…A landmark publication toward the end of 2019 from Princeton University suggests promising PFOA and PFOS transformation to several short‐chain PFAAs facilitated by an autotrophic organism ( Acidimicrobium sp. strain A6) as a first‐time demonstration of bacterially mediated defluorination of PFAAs (Huang and Jaffe ). Partial defluorination has been observed previously during biotransformation of PFAA precursors (such as fluorotelomers) which create PFAAs (e.g., 8:2‐fluorotelomer alcohol partial defluorination to PFOA [Wang et al ]), and there is a host of literature documenting other PFAA precursor biotransformation into terminal PFAAs (Wang et al ; Rhoads et al ; Weiner et al ; Harding‐Marjanovic et al ).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%